A Practical Methodology for Production Data Analysis in Carbonate Reservoirs Using New Decline Type Curves. (8th December 2020) - Jia, Zhihao; Cheng, Linsong; Wang, Peng; Wang, Suran; Jia, Pin
Abstract : Carbonate reservoirs typically have complex pore structures, so the production wells typically have high production in the early production stage, but they decline rapidly. It is highly challenging to achieve accurate interpretation results. In this paper, a new and practical methodology for production data analysis of fractured and fractured-vuggy carbonate reservoirs is proposed. Firstly, analytical solutions to characterize the different multipore media and simulate transient production behavior of fractured and fractured-vuggy carbonate reservoirs during the transient flow regime are presented. Then, a new function f q D and f ′ q D that related to the dimensionless production rate is introduced, and a series of new decline type curves are drawn to make a clear observation of different flow regimes. In addition, the effects of the storativity ratio, interporosity flow coefficient, skin factor, and dimensionless radial distance of external boundary on production performance are also analyzed. Finally, two example wells from the fractured and fractured-vuggy carbonate reservoirs are used to perform rate decline analysis with both the Blasingame type curves and the new type curves. The validation of the new method is demonstrated in comparison to the results of well test interpretation. The results show that the curves of 1 / f ′ q D vs. t D are ∧ -shaped for dual-porosity reservoirs and M -shaped for triple porosity reservoirs and also indicate that the interpreted parameters such as permeability, skin factor, storativity ratio, and interporosity flow coefficient using new decline type curves are aligned well test interpretation. In correlation with other traditional well test analysis, this approach effectively reduces the multisolution probability of interpretation.